ANALISIS PENERAPAN ELECTRONIC GOVERNMENT MELALUI MESIN ANJUNGAN DUKCAPIL MANDIRI (ADM) (STUDI KASUS PADA MAL PELAYANAN PUBLIK KABUPATEN MAGETAN) - Firda Charisma Dewi; Trenda Aktiva Oktariyanda (Universitas Negeri Surabaya, 2022)
Along with the development of technology, the higher the demands of society on the government to provide more effective and efficient services. The Directorate General of Dukcapil seeks to meet the demands of the community by creating a machine called the Independent Dukcapil Pavilion (ADM). With the ADM machine, people can print their own population documents in a short time. Magetan Regency is the first regency/city in Indonesia to procure ADM machines. The first ADM machine in Magetan Regency is located at the Magetan Regency Public Service Mall. The purpose of this study is to describe in detail the implementation of electronic government through the Dukcapil Mandiri Pavilion (ADM) at the Public Service Mall of Magetan Regency. This study uses a qualitative methodology with a descriptive type of research. In collecting data used interview techniques, literature study, observation, and documentation. In analyzing this research, Hafid (2017) uses three success factors for electronic government, which include Institutional Success Factor, Organizational Success Factor, and Technological Success Factor. The results showed that the application of the ADM machine in the Public Service Mall of Magetan Regency had not run completely well. In the institutional success factor, the Disdukcapil leader of Magetan Regency has a large enough influence in the application of ADM machine innovation. The Standard Operational Procedure (SOP) regarding the operation of the ADM machine can be accessed by the public on the official social media of the Magetan Regency Disdukcapil. In the organizational success factor, the organization has not been carried out properly but in the budget aspect there are no obstacles. On the technological success factor, the implementation of ADM machine innovation at the Magetan Regency Public Service Mall has been supported by adequate human resources and equipment, but the print quality is still not good.